2011
DOI: 10.1007/s12613-011-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation behaviors of X80 acicular ferrite pipeline steel

Abstract: The precipitation behaviors of X80 acicular ferrite pipeline steel were investigated by using transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS). The results show that dendritic precipitates in the as-cast steel slabs precipitate mainly in grain boundaries, and these dendritic precipitates dissolve and re-precipitate to two kinds of carbonitrides: Ti-and Nb-rich (Ti, Nb)(C, N) carbonitrides during reheating. Four types of precipitates mainly exist in the hot rolled plate: Ti-rich c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The interest of fine grain in high yield strength steels ferritepearlite structure is therefore double, the interest of fine grains in high yield strength steels with a ferrite-pearlite structure is therefore twofold, hence the interest in the addition of elements allowing the refining of the ferritic grain [2], hence the starting grain austenitic. Grain refining is achieved by the addition of elements forming fine precipitates, which through their interaction with austenitic grain boundaries, prevent the development of these [3].…”
Section: Metallurgical Factors Determining the Properties Of Hsla Steelsmentioning
confidence: 99%
“…The interest of fine grain in high yield strength steels ferritepearlite structure is therefore double, the interest of fine grains in high yield strength steels with a ferrite-pearlite structure is therefore twofold, hence the interest in the addition of elements allowing the refining of the ferritic grain [2], hence the starting grain austenitic. Grain refining is achieved by the addition of elements forming fine precipitates, which through their interaction with austenitic grain boundaries, prevent the development of these [3].…”
Section: Metallurgical Factors Determining the Properties Of Hsla Steelsmentioning
confidence: 99%
“…For example, Zhao et al [20] showed that dendritic precipitates in the as-cast steel slabs precipitate mainly at grain boundaries, and these dendritic precipitates dissolved and re-precipitated into two kinds of carbonitrides: Ti and Nb-rich (Ti, Nb)(C, N) carbonitrides during reheating. Wu et al [14] reported the influence of finish rolling temperatures and tempering temperatures on microstructure and mechanical properties, and found that there were more granular bainite and strain-induced TiC precipitates in the quenched microstructure.…”
Section: Introductionmentioning
confidence: 99%